Radioelement Mapping. - Agency, International Atomic Energy (International Atomic Energy Agency, 2010)
The publication is based on the coordinated work of highly experienced, international experts with the aim of developing a global radioelement map with comparable results from different states. It is intended to support the identification of prospective areas for uranium exploration and mining, and also for environmental actions associated with uranium production and other human activities. The utility of the publication is expected to motivate many states to standardize the status of their radioelement mapping based on the global development and experience.
Keywords: elektronické knihy; electronic books